2014
DOI: 10.1177/1090820x13514077
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Caprini Risk Assessment Model in Evaluation of Non–Venous Thromboembolism Complications in Plastic and Reconstructive Surgery Patients

Abstract: Caprini scores can be used as valuable predictors for some non-VTE postoperative complications (dehiscence, infection, seroma, hematoma, and necrosis). In addition to VTE events, clinicians should pay special attention to clinical signs indicative of the complications listed above when dealing with high-risk, high-Caprini score patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The 2005 Caprini Risk Assessment Model score has been validated in plastic surgery patients and is an effective risk-stratification tool. 28,29 Using this model, essentially, all breast cancer patients undergoing mastectomy are classified as "high risk." 30 In 2011, following the only case (group C) of venous thromboembolism observed at our department, the Caprini score was modified by a multidisciplinary team including hematologist, plastic surgeon, anesthesiologist, and medical internist.…”
Section: Discussionmentioning
confidence: 99%
“…The 2005 Caprini Risk Assessment Model score has been validated in plastic surgery patients and is an effective risk-stratification tool. 28,29 Using this model, essentially, all breast cancer patients undergoing mastectomy are classified as "high risk." 30 In 2011, following the only case (group C) of venous thromboembolism observed at our department, the Caprini score was modified by a multidisciplinary team including hematologist, plastic surgeon, anesthesiologist, and medical internist.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show no relationship between age and risk for complications (45,57,(60)(61)(62)(66)(67)(68)(69)(70)(71), while other studies show that elderly patients have more risk (44,53,63). Diabetes has been associated with postoperative complications after autologous reconstruction, but the results after implantbased breast reconstruction are more conflicting (52,(72)(73)(74)(75). Patients with renal disease seem to be more prone to complications (75,76).…”
Section: The Effect Of Patient Characteristics On Breast Reconstructionmentioning
confidence: 86%
“…Diabetes has been associated with postoperative complications after autologous reconstruction, but the results after implantbased breast reconstruction are more conflicting (52,(72)(73)(74)(75). Patients with renal disease seem to be more prone to complications (75,76). Very little has been published on the history of DVT and postoperative complications, but one study showed an increased risk for thrombosis in free flap surgery in hypercoagulative patients and a very low salvage rate of the affected flaps (77).…”
Section: The Effect Of Patient Characteristics On Breast Reconstructionmentioning
confidence: 99%
“…Unfortunately, no clinically validated protocol dedicated to varicose vein patients undergoing chronic venous disease treatment has been established. The Caprini scale, which is commonly used for surgical patients, has only been validated in some populations, such as intensive care patients, surgical patients and those undergoing plastic surgery [54][55][56][57], but not for patients undergoing varicose vein surgery or receiving minimally invasive treatment for chronic venous disease. As mentioned before, according to the study of Rhee et al, the Caprini risk score should be considered in the EHIT risk assessment [48].…”
Section: Venous Thromboembolism Prophylaxis After Varicose Vein Surgementioning
confidence: 99%